Understandings of climate change articulated by Swedish secondary school students. Issue 4 (2nd October 2017) - Holmqvist Olander, Mona; Olander, Clas
Abstract: This study investigated beliefs about climate change among Swedish secondary school students at the end of their K-12 education. An embedded mixed method approach was used to analyse 51 secondary school students' written responses to two questions: (1) What implies climate change? (2) What affects climate? A quantitative analysis of the responses revealed that 'Earth', 'human' and 'greenhouse effect' were frequent topics regarding the first question, and 'pollution', 'atmosphere' and 'Earth' were frequent regarding the second. A qualitative analysis, based on a 'conceptual elements' framework, focused on three elements within responses: atmosphere (causes and/or consequences), Earth (causes and consequences) and living beings (humans and/or animals and their impacts on climate change). It revealed a predominantly general or societal, rather than individual, perspective underlying students' responses to the second question. The ability to connect general/societal issues with individual issues relating to climate change could prompt students to reflect on the contributions of individuals towards climate change mitigation, thereby constituting a basis for decision-making to promote a sustainable environment. Although the students did not discuss climate changes from an individual perspective, their statements revealed their understanding of climate change as a system comprising various components affecting the overall situation. They also revealed an understanding of the difference between weather and climate.